(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Cancer is a serious issue for society as it is among the top causes of mortality worldwide. The burden of cancer is increasing due to various factors such as the ageing population, unhealthy lifestyles, environmental pollution and more. It is estimated that more than 10 million people will die from cancer-related illnesses in 2021. Therefore, it is important to understand the cancer burden and develop effective prevention strategies to reduce its impact on society (Garland et al., 2012). The cancer burden is the total cost of cancer care, including direct medical costs such as treatments and hospitalizations, indirect costs such as lost productivity due to illness or death, and intangible costs such as suffering and emotional distress. This burden is increasing every year due to advances in medical technology, increased prevalence of certain types of cancer, and rising healthcare costs. While there is no one-size-fits-all solution, there are a variety of prevention strategies that can be used to reduce the threat of cancer. These strategies range from lifestyle changes, such as eating a healthy diet and exercising regularly, to medical interventions, such as vaccines or medications (Bode and Dong, 2009). To reduce this burden, doctors have been looking for ways to prevent and treat cancer. Materials and methods such as “immunotherapy, biomarker therapy, radiation therapy, radiation therapy, chemotherapy, and targeted therapy” are being used to reduce the cancer burden. Also, one such strategy is chemoprevention, which involves using drugs or other agents to reduce the risk of cancer development. Chemoprevention has been studied extensively and is effective in reducing the threat of cancer.